Interleukin-27 Functional Duality Balances Leishmania Infectivity and Pathogenesis - Jafarzadeh, Abdollah; Nemati, Maryam; Chauhan, Prashant; Patidar, Ashok; Sarkar, Arup; Sharifi, Iraj; Saha, Bhaskar (Frontiers in Immunology, 2020)
IL-27 is a cytokine that exerts diverse effects on the cells of innate and adaptive immune systems. Chiefly expressed in macrophages and dendritic cells during the early phase of Leishmania infection, IL-27 contributes to the protection against L. major infection but suppresses the protective Th1 response against L. donovani, L. infantum, L. amazonensis and L. braziliensis infections, suggesting its functional duality. During the late stage of Leishmania infection, IL-27 limits the immunopathogenic reactions and tissue damages. Herein, we analyze the mechanism of the functional duality of IL-27 in the resistance or susceptibility to Leishmania infection, prompting IL-27 for anti-Leishmanial therapy.